PENGARUH MODEL PEMBELAJARAN SSCS TERINTEGRASI STRATEGI MERINGKAS TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK DI KELAS XII - Maresti Feronika Tanaem; Yusnaeni Yusnaeni; Arini Rahma Dhani; Moses Kopong Tokan (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to determine the improvement in students' scientific literacy through the implementation of the SSCS learning model integrated with a summarizing strategy among Grade XII students at SMA Negeri Harekakae during the 2025/2026 academic year. A quasi-experimental research design—specifically a pretest-posttest control group design involving two classes—was employed. The sample was selected using a random sampling technique. The research instrument consisted of a 20-item multiple-choice test covering scientific literacy indicators: identifying scientific problems, interpreting data and drawing conclusions, understanding science concepts, and applying science concepts in real-life situations. The collected data were analyzed using both descriptive and inferential statistics. The results indicated that the normality test values for the experimental class's pretest and posttest were 0.004 (< 0.05) and 0.001 (< 0.05), respectively, while the homogeneity test values for the control and experimental classes' pretests were 0.106 (> 0.05) and 0.028 (< 0.05); thus, the data were neither normally distributed nor homogeneous. Consequently, the analysis proceeded using a non-parametric test, specifically the Mann-Whitney Test. Posttest results showed an average score of 7.76 for the control class and 13.05 for the experimental class, demonstrating that the SSCS learning model integrated with a summarizing strategy had an effect on improving students' scientific literacy.